2-Arylamino-6-ethynylpurines are cysteine-targeting irreversible inhibitors of Nek2 kinase. Issue 6 (22nd May 2020) - Matheson, Christopher J.; Coxon, Christopher R.; Bayliss, Richard; Boxall, Kathy; Carbain, Benoit; Fry, Andrew M.; Hardcastle, Ian R.; Harnor, Suzannah J.; Mas-Droux, Corine; Newell, David R.; Richards, Mark W.; Sivaprakasam, Mangaleswaran; et al.
Abstract : Renewed interest in covalent inhibitors of enzymes implicated in disease states has afforded several agents targeted at protein kinases of relevance to cancers. Abstract : Renewed interest in covalent inhibitors of enzymes implicated in disease states has afforded several agents targeted at protein kinases of relevance to cancers. We now report the design, synthesis and biological evaluation of 6-ethynylpurines that act as covalent inhibitors of Nek2 by capturing a cysteine residue (Cys22) close to the catalytic domain of this protein kinase. Examination of the crystal structure of the non-covalent inhibitor 3-((6-cyclohexylmethoxy-7 H -purin-2-yl)amino)benzamide in complex with Nek2 indicated that replacing the alkoxy with an ethynyl group places the terminus of the alkyne close to Cys22 and in a position compatible with the stereoelectronic requirements of a Michael addition. A series of 6-ethynylpurines was prepared and a structure activity relationship (SAR) established for inhibition of Nek2. 6-Ethynyl- N -phenyl-7 H -purin-2-amine [IC50 0.15 μM (Nek2)] and 4-((6-ethynyl-7 H -purin-2-yl)amino)benzenesulfonamide (IC50 0.14 μM) were selected for determination of the mode of inhibition of Nek2, which was shown to be time-dependent, not reversed by addition of ATP and negated by site directed mutagenesis of Cys22 to alanine. Replacement of the ethynyl group by ethyl or cyano abrogated activity. Variation of substituents on the N -phenyl moiety for 6-ethynylpurines gave further SAR data for Nek2 inhibition. The data showed little correlation of activity with the nature of the substituent, indicating that after sufficient initial competitive binding to Nek2 subsequent covalent modification of Cys22 occurs in all cases. A typical activity profile was that for 2-(3-((6-ethynyl-9 H -purin-2-yl)amino)phenyl)acetamide [IC50 0.06 μM (Nek2); GI50 (SKBR3) 2.2 μM] which exhibited >5–10-fold selectivity for Nek2 over other kinases; it also showed > 50% growth inhibition at 10 μM concentration against selected breast and leukaemia cell lines. X-ray crystallographic analysis confirmed that binding of the compound to the Nek2 ATP-binding site resulted in covalent modification of Cys22. Further studies confirmed that 2-(3-((6-ethynyl-9 H -purin-2-yl)amino)phenyl)acetamide has the attributes of a drug-like compound with good aqueous solubility, no inhibition of hERG at 25 μM and a good stability profile in human liver microsomes. It is concluded that 6-ethynylpurines are promising agents for cancer treatment by virtue of their selective inhibition of Nek2.